2017
DOI: 10.1016/j.fsigen.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Production of high-fidelity electropherograms results in improved and consistent DNA interpretation: Standardizing the forensic validation process

Abstract: Samples containing low-copy numbers of DNA are routinely encountered in casework. The signal acquired from these sample types can be difficult to interpret as they do not always contain all of the genotypic information from each contributor, where the loss of genetic information is associated with sampling and detection effects. The present work focuses on developing a validation scheme to aid in mitigating the effects of the latter. We establish a scheme designed to simultaneously improve signal resolution an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…To calculate an approximation of the LR and the p -value of the LR, CEESIt samples 1 billion (10 9 ) genotypes r i from the set R 1 \{ s }. The LR is calculated as follows: where M = 10 9 [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…To calculate an approximation of the LR and the p -value of the LR, CEESIt samples 1 billion (10 9 ) genotypes r i from the set R 1 \{ s }. The LR is calculated as follows: where M = 10 9 [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Within the context of this study, the nominal NOC is taken to be the TrueNOC as it is reasonable to assume that each contributor's DNA is represented in the signal since it has previously been demonstrated that for this dataset: 1) the RFU signal from a single amplifiable molecule of DNA is fully resolved from noise at these laboratory and AT conditions [20]; 2) the smallest minor contributor of any mixture sample did not fall below 0.016 ng, which is approximately two copies of DNA (NB: some single-source samples were amplified at 0.008 ng); and 3) all 25 s GlobalFiler™ single-source PROVEDIt samples amplified at 0.016 ng or higher rendered RFU signal at a minimum of 12 known allele locations, regardless of the laboratory or sample condition [8]. Though it is likely that some signal at these locations may be attributed to noise, it is unlikely that all 12 can.…”
Section: Nocit Performance and Validationmentioning
confidence: 99%
“…Thus, the dropout rate for the smallest minor in the first bin is expected to range between 28 and 6%. The second bin contains samples with minor contributors that have expected drop-out rates between 0.3 and 6%, whereas the remaining bins all have drop-out rates less than 0.3 % [20] when neither the DNA is degraded or PCR is inhibited. Thus, the bin ranges represent minor contributor quantities exhibiting considerable, some, low and extremely low allelic drop-out due to sampling.…”
Section: Robustness Of Nocit Across Sample Qualitiesmentioning
confidence: 99%
See 2 more Smart Citations